Effect of La-Ni substitution on structural, magnetic and microwave absorption properties of barium ferrite. Issue 6 (15th April 2017) - Shen, Pan; Luo, Juhua; Zuo, Yue; Yan, Zhu; Zhang, Kang
Abstract: In this paper, La-Ni substituted barium ferrite nanoparticles were prepared by a co-precipitation method. The morphology, structure, magnetic and microwave absorption properties of samples were accomplished by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), transmission electron microscope (TEM), vibrating sample magnetometer (VSM) and vector network analysis. From the results evaluation, it can be seen that the magnetoplumbite structure for all of the samples have been formed and the average crystallite sizes of Ba1−x Lax Fe12−x Nix O19 nanoparticles within in the range of 50.9–65.5 nm. Ba0.9 La0.1 Fe11.9 Ni0.1 O19 exhibits a remarkable reflection loss of −13.5 dB at 13.05 GHz with a matching thickness of 1.5 mm. The reflection loss results indicate that Ba0.9 La0.1 Fe11.9 Ni0.1 O19 nanoparticles may be used as a potential for thin microwave absorbers.